Hand-Held Fan Therapy and Changes in Respiratory Parameters in Hospitalized Patients with Congestive Heart Failure: A Nursing Case Series - Ria Ika Imelda; Rusmawati Sitorus; Fitri Novitasari; Helena Nila Katu; Apriani Angelica (STIKep PPNI Jawa Barat, 2026)
Background: Congestive heart failure (CHF) is a progressive clinical syndrome characterized by impaired cardiac function and reduced ability to meet metabolic demands. Dyspnea is one of the most frequent symptoms and is commonly identified in nursing practice as an ineffective breathing pattern. Supportive non-pharmacological interventions may assist in relieving respiratory distress. Hand-held fan therapy delivers airflow to the facial area and has been suggested as a simple method to reduce breathlessness. Objective: To describe changes in respiratory rate and oxygen saturation among patients with CHF following the application of hand-held fan therapy as part of inpatient nursing care. Methods: A descriptive case series was conducted using the nursing process framework. Three hospitalized CHF patients with ineffective breathing patterns were observed in a cardiovascular ward at RSUD Koja Hospital, North Jakarta. Hand-held fan therapy was applied for approximately five minutes per session. Respiratory rate and oxygen saturation were monitored before and after the intervention period. Results: All patients showed tachypnea at baseline (28 breaths/min). After repeated application of hand-held fan therapy, respiratory rates decreased consistently to 22 breaths/min. Oxygen saturation improved modestly from 93–94% to approximately 95%. Conclusion: Hand-held fan therapy was associated with improved breathing patterns and oxygenation in patients with CHF. This intervention may be considered a supportive nursing strategy for managing dyspnea